Brand champions : how superheroes bring brands to life - Buckingham, Ian P., 1967- (Houndmills, Basingstoke, Hampshire : Palgrave MacMillan, 2011)
'A case-study based guide which showcases the individuals within organizations who nurture and sustain brands and bring them to life through their everyday performance. Critical enough to remain credible yet overwhelmingly positive, it is a charismatic illustration of how to achieve true brand engagement'--
Includes bibliographical references and index.
Keywords: Brand name products; Branding (Marketing); Brand name products -- Case studies; Branding (Marketing) -- Case studies